Sick Building Syndrome in Public Buildings and Workplaces - Jansz, Janis (World Safety Organization, 2011)
This paper traces the history of sick building syndrome from the book of Leviticus in the Bible to the present day. It identifies health effects that can be caused by sick building syndrome factors and risk control measures to use to meet the legal requirements to have a safe place to work in and a healthy place to live in.